Implementation of an Independent Curriculum In Improving The Quality Of Learning - Harlen Simanjuntak; Juliper Nainggolan (LPPM Universitas PGRI Sumatera Barat, 2024)
Prof Dr S Nasution in his book entitled Curriculum and Teaching states that the curriculum is a series of plans to facilitate the teaching and learning process. The plans prepared are the responsibility of educational institutions and the teachers there. Meanwhile, in the National Education System Law Number 20 of 2003, article 1 number 19, it is stated that the curriculum is a set of arrangements and plans regarding objectives, content and learning materials as well as the methods used to guide learning activities. to achieve educational goals. It is important for every school to have a curriculum as a guide for teachers. It could even be said that if there is no curriculum then learning at school cannot run well. This research uses a data collection approach using participant observation, documentation studies, and interviews. Here there are 3 aspects in implementing an independent curriculum, namely planning the implementation of an independent curriculum, implementing an independent curriculum and evaluating independent curriculum learning. Independent curriculum planning at SD Negeri 060833 Medan Petisah District, Medan City and analyzing learning outcomes (CP) to formulate learning objectives and the flow of learning objectives, planning diagnostic assessments, developing learning modules that adapt learning to the stages and characteristics of student achievement and planning formative and summative assessments . Implementation of an independent curriculum at SD Negeri 060833 Medan Petisah District, Medan City by carrying out diagnostic assessments, carrying out learning according to project-based teaching modules, as well as carrying out formative and summative assessments. Evaluation of learning to implement the independent curriculum at SD Negeri 060833 Medan Petisah District, Medan City, by carrying out diagnostic assessments, carrying out and processing formative and summative assessments. The author suggests that SD Negeri 060833 Medan Petisah District, Medan City, continue to monitor and develop itself by continuing to improve the curriculum for better school quality. Apart from that, the success of schools in implementing an independent curriculum must also be socialized to schools that have not implemented it.